Breathing Exercises in Gastroesophageal Reflux Disease: A Systematic Review - Zdrhova, Lucie; Bitnar, Petr; Balihar, Karel; Kolar, Pavel; Madle, Katerina; Martinek, Milan; Pandolfino, John Erik; Martinek, Jan (Dysphagia, 2023)
The pathogenesis of gastroesophageal reflux disease (GERD) is multifactorial. The severity of abnormal reflux burden corresponds to the dysfunction of the antireflux barrier and inability to clear refluxate. The crural diaphragm is one of the main components of the esophagogastric junction and plays an important role in preventing gastroesophageal reflux. The diaphragm, as a skeletal muscle, is partially under voluntary control and its dysfunction can be improved via breathing exercises. Thus, diaphragmatic breathing training (DBT) has the potential to alleviate symptoms in selected patients with GERD. High-resolution esophageal manometry (HRM) is a useful method for the assessment of antireflux barrier function and can therefore elucidate the mechanisms responsible for gastroesophageal reflux. We hypothesize that HRM can help define patient phenotypes that may benefit most from DBT, and that HRM can even help in the management of respiratory physiotherapy in patients with GERD. This systematic review aimed to evaluate the current data supporting physiotherapeutic practices in the treatment of GERD and to illustrate how HRM may guide treatment strategies focused on respiratory physiotherapy.
Keywords: Esophagogastric Junction; Breathing Exercises; gastroezofageální reflux; Gastroesophageal Reflux; gastroezofageální junkce; Humans; lidé; Manometry; manometrie; dechová cvičení